2017
DOI: 10.2118/185185-pa
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behavior and Viscous-Oil-Microdisplacement Characteristics of Hydrophobically Modified Partially Hydrolyzed Polyacrylamide in a Repeatable Quantitative Visualization Micromodel

Abstract: Summary To profoundly investigate the flow behavior and viscous-oil-microdisplacement characteristics of hydrophobically modified partially hydrolyzed polyacrylamides (HMHPAMs) as well as the effect of associating monomer content on those behaviors and characteristics, compared with partially hydrolyzed polyacrylamide (HPAM), the flow experiments through three serial mounted flat-sand-inclusion micromodels and the viscous-oil-microdisplacement experiments in both homogeneous and interstratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Comparing with HPAM, the resistance factors and residual resistance factors produced by HMHPAMs are higher than those of HPAM due to an increase of aggregate size of HMHPAMs. The microdisplacement experiments indicated that the HMHPAMs could move deep into the porous media of reservoirs [7]. Moreover, the existing literature also reported that HMHPAMs had more stable displacement front and easily formed a piston-like displacement.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Comparing with HPAM, the resistance factors and residual resistance factors produced by HMHPAMs are higher than those of HPAM due to an increase of aggregate size of HMHPAMs. The microdisplacement experiments indicated that the HMHPAMs could move deep into the porous media of reservoirs [7]. Moreover, the existing literature also reported that HMHPAMs had more stable displacement front and easily formed a piston-like displacement.…”
Section: Introductionmentioning
confidence: 85%
“…However, with the rapid growth in energy demand and a depletion of conventional oil, the development of nonconventional energy sources, such as viscous oil, bitumen, and shale oil, is significant for the entire petroleum industry [4][5][6]. The viscous oil is mainly distributed in many basins, especially in the region of Middle East, North America, and South America [7,8]. Reports by the U.S. Department of Energy showed that 40% of the 900-1300 billion barrels of reserves in the world is viscous oil and ultraheavy oil [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most Chinese oil field reservoirs are continental deposits with serious heterogeneity and prominent interlayer contradictions. Under the traditional injection method, 7 ASP solution is injected into high‐permeability reservoirs in large amounts, 8‐10 while it is injected into low‐permeability reservoirs in small amounts, and the compatibility of low‐permeability reservoirs with ASP solution is poor, 11‐13 resulting in a poor production degree and low total oil recovery in low‐permeability reservoirs. Therefore, in order to improve the total oil recovery of heterogeneous oil layers, a layered injection method which is for the different levels of oil permeability is proposed for Daqing Oilfield, and the method is shown in Figure 1 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…An ASP solution with a high molecular weight and high concentration can greatly improve oil recovery in high permeability oil layers [4]. However, for heterogeneous reservoirs, the injection effect of the displacement agent in high permeability reservoirs is better and the injection amount is greater [5,6], which results in less displacement agent flowing into low permeability reservoirs, and it is difficult for high molecular weight and high concentration displacement agents to enter low permeability reservoirs [7], resulting in a low overall crude oil recovery. For this reason, Daqing Oilfield has proposed a type of injection technology.…”
Section: Introductionmentioning
confidence: 99%